Perspectives on strategy - Gray, Colin S. (Oxford University Press, 2013)
Perspectives on Strategy examines in depth five aspects of strategy from the perspectives of: intellect, morality, culture, geography, and technology. The author asks and answers the most challenging and rewarding questions that can be posed in order to reveal the persisting universal nature, but ever changing character, of strategy.